2020
DOI: 10.1088/1757-899x/955/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of aerogel in building construction –A Review

Abstract: Aerogel are synthetic light weight material obtained in a gel form with gas without any shrinkage. The first form of aerogel is produced by using Silica gels. There are several other types of aerogels such as carbon-Based aerogel, clay-Based aerogel and silica-Based aerogel. Aerogel are mostly in solid form with extremely low conductivity and possess very low density and high porosity ( < 100nm). Aerogel are water repellent material. In recent years, Aerogel have attracted towards various sectors, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…One such smart material that has caught the interest of the scientific community is aerogel. Aerogelbased materials are used for highly efficient thermal insulation in the construction sector, as it has extremely low thermal conductivity and highest porosity (Günther et al, 2020;Shanmugam et al, 2020). Aerogel acts as an insulation, which can improve building's energy efficiency, reduce cost of heating and cooling, and also enhance comfort for its occupants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One such smart material that has caught the interest of the scientific community is aerogel. Aerogelbased materials are used for highly efficient thermal insulation in the construction sector, as it has extremely low thermal conductivity and highest porosity (Günther et al, 2020;Shanmugam et al, 2020). Aerogel acts as an insulation, which can improve building's energy efficiency, reduce cost of heating and cooling, and also enhance comfort for its occupants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aerogel is a synthetic gel composed of porous solid materials and a gas dispersion phase with ultralow density, which is also known as “frozen smoke”. , Aerogels have become one of the research hotspots in the field of materials science due to their abundant raw materials, various preparation methods, and unique properties. , It has been nearly 90 years since the initial use of sodium silicate as a raw material to obtain SiO 2 aerogels through supercritical drying technology . The types of aerogels include SiO 2 aerogels, biomass-based aerogels, metal oxide aerogels, , polymer aerogels, , carbon aerogels, ceramic aerogels, , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Shanmugam et al 2020 [11] in a study to replace materials with aggregates to reduce weight and use distributed fibers, as well as to compare its properties with conventional concrete, it was found that mixtures containing fibers had higher tensile strength and four compressive strengths, bending strengths, and tensile strengths when tested on samples aged 7 and 28 days.…”
mentioning
confidence: 99%